1998
DOI: 10.1136/jcp.51.9.676
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis G virus infection in lymphoma and in blood donors

Abstract: Aims-To determine whether the recently described flavivirus, hepatitis G virus (HGV), might contribute to the pathogenesis of lymphoma by testing for the presence of HGV RNA in sera from patients attending lymphoma clinics; to compare the incidence of HGV RNA in lymphoma patients with that in normal blood donors; and to look for potential risk factors for HGV infection and for evidence of hepatic disease in the HGV positive patients. Methods-Sera were examined from 76 patients with lymphoma and 100 blood donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…The positive associations observed in the Canadian study and ours are consistent with results from previous but less definitive case-control studies (18–24). Some of these studies included NHL cases coinfected with HCV (18, 21, 24), and the controls in some studies were drawn from convenience groups (blood donors, cancer patients) which were not representative of the source population giving rise to the NHL cases (18, 20, 21, 23). …”
Section: Discussionmentioning
confidence: 99%
“…The positive associations observed in the Canadian study and ours are consistent with results from previous but less definitive case-control studies (18–24). Some of these studies included NHL cases coinfected with HCV (18, 21, 24), and the controls in some studies were drawn from convenience groups (blood donors, cancer patients) which were not representative of the source population giving rise to the NHL cases (18, 20, 21, 23). …”
Section: Discussionmentioning
confidence: 99%
“…A high incidence of past GBV‐C infection might be present in patients with B cell‐NHLs . Some studies suggested an association between GBV‐C infection and NHL , but other authors could not make the same observation . Many of these studies comprised a small number of patients or lacked of controls, so this still represents a controversial issue.…”
Section: Discussionmentioning
confidence: 99%
“…and Ellenrieder et al .,24 but these studies were based on small numbers of patients and lacked controls. Others25–29 have shown a higher prevalence of GBV‐C RNA in cases vs . controls, but many of these studies were limited in sample size.…”
mentioning
confidence: 95%